PHYSICALPROPERTIES AND SOLUBILITY OF C02 IN AQUEOUS TETRABUTYLAMMONIUM HYDROXIDE, AQUEOUS PIPERAZINE AND THEIR AQUEOUS BLENDS - SAFDAR, RIZWAN (2014)
Ionic Liquids (ILs) have attracted widespread attention as an alternative class of solvent for C02 capturing from different streams. Among the ILs, ammonium based appear as a promising class for C02 absorption due to water miscibility, water stability, comparatively low viscosity, low density and large free volume. For design of new acid gas removal equipments, thermophysical data is essential and before using the ILs for C02 separation it is essential to have knowledge of solubilityof C02 in ILs. In present work the Physical properties (density, viscosity and refractive index) of aqueous solutions of tetrabutylammonium hydroxide (TBAOH), aqueous solution of Piperazine (PZ) and aqueous blend of TBAOH and PZ have been measured in the temperature range of 303.15 to 333.15 K. The C02 solubility in aqueous solutions of TBAOH, aqueous solution of PZ and aqueous blends of TBAOH and PZ was determined by using high pressure solubility cell at temperatures (303.15, 313.15 and 333.15 K) and pressure range from 2 to 10.37 bar. From the measurements it was found that an aqueous solution of TBAOH with higher concentration has lower density than all other solutions.